2019
DOI: 10.1186/s12875-019-0967-y
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for primary care provision in Germany – a discrete choice experiment

Abstract: Background Primary care is a central element of healthcare and addresses the main health problems of the population. While primary care gains in importance due to an aging population, there is an ongoing debate on physician shortages in German rural regions. The study aims on analyzing the population’s preferences on primary healthcare and, therefore, on helping policy makers to make care delivery more responsive to patients’ needs when planning political reforms of primary care. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Further, we also found different preferences in the way of service delivery between residents and healthcare providers. Similar to results from previous studies (16), our findings revealed that home visits significantly influenced the residents' preference for FDCS. The residents included in our study were key population, such as the elderly people, who generally have high healthcare needs and desire more home visit service.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, we also found different preferences in the way of service delivery between residents and healthcare providers. Similar to results from previous studies (16), our findings revealed that home visits significantly influenced the residents' preference for FDCS. The residents included in our study were key population, such as the elderly people, who generally have high healthcare needs and desire more home visit service.…”
Section: Discussionsupporting
confidence: 90%
“…Only one study to data measured the supply preferences from the perspective of healthcare providers (15). Meanwhile, similar studies have been conducted in other countries (16)(17)(18)(19)(20); nevertheless, considering that patients and healthcare providers references may be subjected to cultural and policy differences, the applicability of research from overseas to China mainland may be limited. More importantly, given the asymmetry of information between consumer and provider, it is not always clear that observed healthcare consumption is based on consumers' preferences and choice alone (21).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PHC institutions should set up chronic disease clinics for asthma and COPD, provide family practice contract service and carry out screening for chronic diseases, as well as health education in the community. Last, a discrete choice experiment revealed that preferences for primary care were significantly influenced by the provision of home visits, the distance to clinics, the clinics’ opening hours, and the diagnostic facilities in clinics [ 25 ]. As a consequence, PHC doctors could take the initiative to provide home visits, especially for the vulnerable group of older, multimorbid and immobile persons who have specific needs concerning care provision, or PHC doctors could conduct telephone interviews to facilitate monitoring of patients’ medication and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They also allow for closer cooperation with non-medical primary health care providers, including home care nursing services or pharmacies [ 35 , 36 ]. Multi-professional primary health care teams involving nurses are only rarely established in standard care but are being tested increasingly (partially as pilot projects) in some regions [ 3 , 37 ]. There are projects, too, in which different health professions cooperate to provide primary care while practicing in institutionally distinct facilities (such as family doctor practices and home care services).…”
Section: Methodsmentioning
confidence: 99%